The Phenomenon of Instant Interpretation on TikTok and the Risk of Reducing the Meaning of Al-Quranic Verses among the Younger Generation - Akram, Akram; Djafar, Arinil Hidayah; Rustan, Edhy; Harun, Amrullah (Jurnal El-Thawalib, 2025)
The development of social media, especially TikTok, has encouraged the emergence of the phenomenon of "instant interpretation" presented through short and aesthetic videos. This phenomenon is increasingly popular among the younger generation and has the potential to influence the way they understand the Qur'an. This study aims to analyze the characteristics of instant interpretation content on TikTok and identify forms of verse misunderstandings experienced by the young generation in Palopo City. This research is a qualitative study employing a phenomenological approach to explore subjective receptive experiences. Data sources consisted of 19 informants selected through purposive sampling, including 15 active TikTok users, 2 young ustaz, and 2 academics as triangulation. Data collection techniques involved content observation, in-depth interviews, and digital documentation. Data analysis followed the Miles, Huberman, and Saldana interactive model. The results of the study show that the content of instant interpretation is dominated by aesthetic visuals that have minimal methodological references so as to produce partial and emotional understanding. The risk of misunderstanding is influenced by the format of short videos, pseudo-creator authority, TikTok algorithms, and low digital and religious literacy. The findings of this study affirm the importance of strengthening religious and digital literacy to prevent the narrowing of the meaning of verses in the digital space and contribute to the development of contemporary interpretation studies and digital da'wah